Pengaruh Likuiditas dan Pertumbuhan Aset terhadap Kebijakan Dividen dengan Ukuran Perusahaan sebagai Variabel Moderating - adillia cahya ramadhani (Universitas Veteran Bangun Nusantara, 2021)
The purpose of this study was to examine the effect of liquidity ratios and asset growth with firm size as a moderating variable. This research was conducted on property, real estate and building construction sector companies listed on the Indonesia Stock Exchange in 2013-2019. Determination of the sample using purposive sampling technique. The number of samples selected amounted to 80 data. The data was processed using multiple linear regression analysis statistical tests to answer hypothesis 1 and hypothesis 2, then multiple linear regression analysis with moderated regression analysis was used to answer hypothesis 3 and hypothesis 4. Based on the test results, this study shows that liquidity and asset growth have a positive effect on policy dividends and firm size are not able to moderate the relationship between liquidity to dividend policy and asset growth to dividend policy. Keywords: liquidity, asset growth, firm size, dividend policyU